If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19x + -13 = 25 Reorder the terms: -13 + 19x = 25 Solving -13 + 19x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 19x = 25 + 13 Combine like terms: -13 + 13 = 0 0 + 19x = 25 + 13 19x = 25 + 13 Combine like terms: 25 + 13 = 38 19x = 38 Divide each side by '19'. x = 2 Simplifying x = 2
| 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) | | 2x+3(1x-10)=45 | | (x^2+1)= | | 2x+3(x-10)=-45 | | y=-0.2*x+520.4 | | 1x-5(x+2)=26 | | 6*6+7= | | 2sen^2x-senx-1=0 | | 5/678 | | 5/6.35 | | 5/6•35 | | 2y-50+5y-17=180 | | 3=5-3/4 | | 5x-8(x+5)= | | 3x(x+0)=0 | | 1/3,4 | | 2x+3=-(x+1) | | 3(k-6)-(-3k-8)=5k | | 35,5/6 | | rs-6r+st-6t= | | y=2x+6(6*7) | | 0=3y^2+30y+70 | | 5(n+2r)+3n= | | 0.3+0.6=1.5 | | 5x-3-2x=x+11 | | 2(3x-1)=8x+11 | | What*12=400 | | 5=v-2 | | 7x/6-3=25 |